Investigating a microbial approach to water conservation: Effects of Bacillus subtilis and Surfactin on evaporation dynamics in loam and sandy loam soils - Gutierrez, Moises M.; Cameron-Harp, Micah V.; Chakraborty, Partha P.; Stallbaumer-Cyr, Emily M.; Morrow, Jordan A.; Hansen, Ryan R.; Derby, Melanie M. (Frontiers in Sustainable Food Systems, 2022)
Semi-arid regions faced with increasingly scarce freshwater resources must manage competing demands in the food-energy-water nexus. A possible solution modifies soil hydrologic properties using biosurfactants to reduce evaporation and improve water retention. In this study, two different soil textures representative of agricultural soils in Kansas were treated with a direct application of the biosurfactant, Surfactin, and an indirect application via inoculation of Bacillus subtilis. Evaporation rates of the wetted soils were measured when exposed to artificial sunlight (1000 W/m2) and compared to non-treated control soils. Experimental results indicate that both treatments alter soil moisture dynamics by increasing evaporation rates by when soil moisture is plentiful (i.e., constant rate period) and decreasing evaporation rates by when moisture is scarce (i.e., slower rate period). Furthermore, both treatments significantly reduced the soil moisture content at which the soil transitioned from constant rate to slower rate evaporation. Out of the two treatments, inoculation with B. subtilis generally produced greater changes in evaporation dynamics; for example, the treatment with B. subtilis in sandy loam soils increased constant rate periods of evaporation by 43% and decreased slower rate evaporation by 49%. In comparing the two soil textures, the sandy loam soil exhibited a larger treatment effect than the loam soil. To evaluate the potential significance of the treatment effects, a System Dynamics Model operationalized the evaporation rate results and simulated soil moisture dynamics under typical daily precipitation conditions. The results from this model indicate both treatment methods significantly altered soil moisture dynamics in the sandy loam soils and increased the probability of the soil exhibiting constant rate evaporation relative to the control soils. Overall, these findings suggest that the decrease in soil moisture threshold observed in the experimental setting could increase soil moisture availability by prolonging the constant rate stage of evaporation. As inoculation with B. subtilis in the sandy loam soil had the most pronounced effects in both the experimental and simulated contexts, future work should focus on testing this treatment in field trials with similar soil textures.